THU0072 ULTRASOUND PREDICTS IMMINENT PROGRESSION TO ARTHRITIS IN ANTI-CCP POSITIVE AT-RISK INDIVIDUALS. (June 2019) - Duquenne, Laurence; Mankia, Kulveer; Nam, Jacqueline; Pentony, Peta; Garcia-Montoya, Leticia; Dimatteo, Andrea; Hunt, Laura; Emery, Paul
Abstract : Background: Ultrasound (US) Power Doppler (PD) signal is predictive for the development of inflammatory arthritis (IA) in anti-cyclic citrullinated protein antibodies positive (CCP+) individuals with musculoskeletal (MSK) symptoms but no clinical synovitis (CS) [1]. Our previous data showed a late increase in the overall US inflammation before arthritis development, suggesting that a sub-clinical phase of synovitis could be detected [2]. This abstract describes the prediction of PD abnormalities in the months following US scan. Objectives: 1. Presence of PD in one joint is predictive of imminent progression to IA in the next 3months. 2. A rise in the number of joints with presence of PD increases the odds of progression to IA. Methods: In a single-centre prospective observational cohort between June 2008 and December 2018, 307 CCP+ patients with a new MSK symptom but no synovitis were followed until CS occurred. Clinical and US findings were analysed. Following our previous study, we compared progression in the 3, 12 or >12 months after a US scan. 38 joints were included in the analysis (MTPs, hands, wrists, elbows, ankles and knees). Patients with palindromic rheumatism were excluded. Results: Data from 96 CCP+ at-risk patients who developed CS (progressors) are compared to 211 CCP+ patients who did not (non-progressors). Age and gender are similar, the mean follow-up of the non-progressors is higher, with significantly more smokers and high titre CCP in the progressors group (Table1 ). Overall, progressors have more joints with PD than non-progressors (Figure1 ). Patients with PD in one joint are more likely to develop CS in the following 3 months compared to those without PD (OR 7.52) and this remain significant when only the hands and wrists are included (Table2 ). The highest OR is shown when PD≥2 is found in at least one wrist. Similarly, there is a significant but smaller prediction of progression between 3 to 12 months after US (Table2 ). When a new joint develops PD, the likelihood of progression to IA within the next 3 months increases (Table2 ). This is especially predictive with wrists involvement (OR 3.10). Prediction of progression between 3 to 12 months before CS is significantly different between groups, with a higher OR for the wrists. Conclusion: The presence of PD in one joint and every new joint with PD are both predictive of progression to IA within the next 3months. These results should lead to a logical programme for therapy and follow -up. References: [1] Nam J. et al., US findings predict progression to inflammatory arthritis in anti-CCP positive patients without CS. Ann Rheum Dis, 2016. 75(12). [2] Pentony P,  et al.,  Sequential US shows a late increase in inflammatory burden in anti-ccp positive patients with non-specific MSK symptoms just before progression to IA. Ann Rheum Dis, volume 77, year 2018 Disclosure of Interests: Laurence Duquenne: None declared, Kulveer Mankia Grant/research support from: Research support from BMS and Lilly, Speakers bureau: Honoraria from Abbvie, UCB, Jacqueline Nam: None declared, Peta Pentony: None declared, Leticia Garcia-Montoya: None declared, Andrea DiMatteo: None declared, Laura Hunt: None declared, Paul Emery Grant/research support from: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, Roche, Consultant for: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, UCB, Roche, Novartis, Gilead, Samsung, Sandoz and Lilly